Is Whole‐Brain Radiotherapy for Brain Metastases an Overestimated Therapy? A Retrospective Study of Real‐World Data Using Landmark Analyses - Florian Hoelzl; Oliver Koelbl; Isabella Gruber (Cancer Medicine)
ABSTRACT Background The role of whole‐brain radiotherapy for patients with brain metastases is changing as immunotherapy and molecularly targeted therapies advance. However, whole‐brain radiotherapy continues to be part of the multimodal concept. Methods This retrospective study included 285 patients who received whole‐brain radiotherapy for brain metastases, using a median dose of 30 Gy. The study analyzed prognostic factors for survival using Cox regression analyses, while two landmark analyses, reflecting a minimum survival of 60 and 90 days, accounted for early deaths. Neurological symptoms were compared before and after treatment using the McNemar test. Results The median patient age was 62 years. Non‐small cell lung cancer (n = 95), breast cancer (n = 53), and small cell lung cancer (n = 48) were the most frequent cancer types. Median survival was 4.3 months (interquartile range 1.8–11.1). In the multivariable Cox regression model, patients who received additional immunotherapy/molecularly targeted therapy had a higher chance of survival than others. Overall survival was influenced by control of primary cancer, extracranial metastases, age, Karnofsky performance status, and number of brain metastases. The 90‐day landmark analysis included 181 patients who survived at least 90 days, reflecting that 104 patients (36.5%) died within the first 90 days. The 90‐day landmark analysis confirmed all predictive variables for survival. Patients who died before the 90‐day landmark endpoint had more brain metastases, lower Karnofsky performance status, higher age, and were less frequently treated with immunotherapy/molecularly targeted therapy than those surviving at least 90 days. The treatment significantly improved neurological symptoms. Conclusion These results indicate an insufficient patient selection, as one‐third of patients treated with whole‐brain radiotherapy died within 90 days. However, neurological symptoms improved, and the addition of immunotherapy and/or molecularly targeted therapy to whole‐brain radiotherapy was associated with better survival. Patients receiving whole‐brain irradiation should be more carefully selected. Trial Registration ClinicalTrials: 24‐3626‐104